Предмет: Алгебра, автор: markes78

а) 3х(2х-1)-6х(7+х)=90 б)1,5x(3+2x)=3x(x+1)-30 в)5x(12x-7)-4x(15x--11)=30+29x г)24х-6х(13х-9)=-13-13х(6х-1) объясните пожалуйста подробно

Ответы

Автор ответа: kiskam
0

a)\3x(2x-1)-6x(7+x)=90\6x^2-3x-42x-6x^2=90\-45x=90\x=frac{90}{-45}\x=-2\\</var><var>\b)\1,5x(3+2x)=3x(x+1)-30\4,5x+3x^2=3x^2+3x-30\3x^2-3x^2+4,5x-3x=-30\1,5x=-30\x=frac{-30}{1,5}\x=-20\\B)\5x(12x-7)-4x(15x-11)=30+29x\60x^2-35x-60x^2+44x=30+29x\9x-29x=30\-20x=30\x=frac{30}{-20}\x=-1,5\\ r)\24x-6x(13x-9)=-13-13x(6x-1)\24x-78x^2+54x=-13-78x^2+13x\24x-78x^2+78x^2+54x-13x=-13\65x=-13\x=frac{-13}{65}\x=frac{-1}{5}\x=-0,2 

Похожие вопросы